PENGARUH VIRAL MARKETING DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN RAZWA CAFÉ NAGARAKEMBANG: (Studi Kasus di Razwa Café Nagarakembang Majalengka) - Hendriyadi, Resnu; Harjadi, Dikdik; Gunawan, Wely Hadi (FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KUNINGAN, 2023)
This research raises problems related to the consumer purchasing decisions of Razwa Café Nagarakembang Majalengka which have not been maximized. The purchasing decision problem can be determined by various factors, including viral marketing and store atmosphere. The aim of carrying out this research is to determine the influence patterns of viral marketing and store atmosphere on purchasing decisions, both simultaneously and partially. There are three hypotheses that will be tested, namely viral marketing and store atmosphere influence purchasing decisions together, and viral marketing and store atmosphere have a positive influence on purchasing decisions individually. This research uses a quantitative method approach. The sample determination in this research was carried out efficiently based on random sampling. The sample size used was 100 respondents. The data collection technique is questionnaire-based with data analysis techniques using multiple linear regression models. The research results show that: (1) the viral marketing and store atmosphere variables simultaneously have a significant effect on purchasing decisions, (2) the viral marketing variable partially has a significant effect in a positive direction on purchasing decisions, (3) the store atmosphere variable partially has a significant effect in a positive direction on purchasing decisions. Keywords: viral marketing; store atmosphere; purchase decision